LITERATURE CHILDREN - CHILD AS PROTAGONIST - Silva, Wellington Amancio do (Journal of Humanity, 2014)
This paper aims to contribute to issues related to social representations of children through the lens of the adult world; we recommend that fosters the childs opportunity to be author and co-author (protagonist) in the production of childrens literature and is known to be beyond their textual production considering that all production of children in school (painting, scribbling, drawings, sketches of letters and various signs) is recognized as childrens literature.Â